Prevalence and Morphological Types of Anemia Among Children 6 to 59 Months in an Urban Hospital of Sudurpaschim, Nepal - Awale, Rubee; Shah, Amrendra; Mishra, Ujjwal (Birat Journal of Health Sciences, 2025)
Introduction: Anemia is the major health concern worldwide and in Nepal. Geo-ecological constraint of Sudurpashchim province of Nepal has detached it from various facilities in health and nutrition. Mainly children less than 5 years have major health problems leading to high burden of anemia. Limited study is conducted in this region, so this study will help to determine the prevalence and morphological types of anemia in this region so that government will provide necessary preventive strategy and management to the area of need. Methods: This was the retrospective cross-sectional descriptive study conducted in Lal Ratna Hospital (LRH) between 14th February 2023 to 13th February 2024 among children between 6 to 59 months after ethical approval from NHRC. Sample size was calculated using single proportion formula with 95% Confidence interval and 6% error. Convenience sampling method was used. Results: Prevalence of anemia was 249 (68.40%), male 164 (65.86%) was more anemic than female 85(34.14%). The children between 12 to 23 months were more anemic 76 (30.5%) followed by 6 to 11 months, 68 (27.3%) and signifies children less than 2 years are more anemic. Most of the children were mild anemic 125(50.2%), followed by 124 (49.8%) moderate and none were severely anemic. Morphologically, microcytic hypochromic anemia was the commonest type, 159 (63.9%) followed by microcytic normochromic 57 (22.9%). Children not dewormed, 152 (61.05%), were more anemic. Conclusions: There is high burden of anemia among the children of Sudurpaschim, indicating poor health and nutritional status.